ANALYSIS OF THE MARKETING STRATEGY OF SASADAKOPI COFFEE SHOP ON CONSUMER BEHAVIOR IN MEDAN, NORTH SUMATRA - Dhalimunthe, M. Ikbal Nur Irsyad; Harahap, Gustami; Nurcahyani, Marizha (Distribusi - Journal of Management and Business, 2025)
Sasadakopi is a coffee shop founded by Devi Siburian. She is also the owner and manager of the coffee shopased on interviews with owners and observations, this business was established on October 26 2019 at Sei Bahorok street No. 21, Babura, Medan Baru, North Sumatra. Every week, Sasadakopi is busy with customers . Most of the customers are teenagers and students. Corporate strategy is a pattern or a plan that integrates the main goals or company policies with a series of actions in a binding agreement. In other words, a marketing strategy is a strategy used to gain profits in business by paying attention to business relationships with consumers. Based on the results of the research, analysis and evaluation that have been carried out, it can be concluded that Sasadakopi Roastery has successfully executed their marketing strategy. In its strategy, Sasadakopi focuses on introducing the taste of coffee that is different from other coffee shops to the consumers.